The Implementation of the Book “Washoya Al-Abaa’ lil Abnaa’” in Improving Ethics in Madrasah - Rosid, Fathor; Masrurah, Waqi'atul; Andawiyah, Robiatul; Abidin, Zainal; Hamdani, Hamdani; Long, Ahmad Sunawari (Al-Jadwa: Jurnal Studi Islam, 2025)
Madrasah institutions are often perceived to lag behind state education, yet they possess unique characteristics that foster religious knowledge and ethical development in students. The “Washoya Al-Abaa’ lil Abnaa’” book serves as an essential teaching resource aimed at improving student ethics within the Islamic educational framework. This study aims to explore the implementation of the Washoya book and its impact on enhancing student ethics at Madrasah Ittihadzul Mudzakkirin. Using a qualitative descriptive approach, data were collected through interviews and documentation from teachers, students, and the community. The findings reveal that the Washoya book promotes good behavior among students, demonstrating significant ethical improvement both within the madrasah and the wider community. Supporting factors include strong collaboration among educators and guidance from leadership, while inhibiting factors arise primarily from influences outside the learning environment. Community feedback underscores the effectiveness of these ethical teachings, suggesting that students are adopting better practices influenced by the book’s content. This research contributes to the understanding of ethical education in Islamic institutions and highlights the importance of ongoing development in the study of the Washoya book.